2006
DOI: 10.1177/0042085906287902
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Children

Abstract: In spite of the most adverse circumstances, some children manage to survive and even thrive, academically and socially, into adulthood. A complex array of individual, family, and community factors has been identified that best explains resilience and lays the foundation for programs and interventions targeted at fostering the development and maintenance of resilience in at-risk youth. The literature is reviewed to identify and explain those factors, discuss their mutual interaction, and explain their implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(71 citation statements)
references
References 66 publications
3
55
0
13
Order By: Relevance
“…This hypothesis was supported by our finding, which replicates previous findings in other samples (Sun and Stewart, 2007;Gooding et al, 2011;Wagnild, 2011). It contradicts the findings of researchers (Condly, 2006;Schoon, 2006;Riches et al, 2009). Since adolescence is usually understood to be a period of storm and stress, the adolescent may not have acquired the cumulative capacity for thriving that may characterise young adulthood.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This hypothesis was supported by our finding, which replicates previous findings in other samples (Sun and Stewart, 2007;Gooding et al, 2011;Wagnild, 2011). It contradicts the findings of researchers (Condly, 2006;Schoon, 2006;Riches et al, 2009). Since adolescence is usually understood to be a period of storm and stress, the adolescent may not have acquired the cumulative capacity for thriving that may characterise young adulthood.…”
Section: Discussionmentioning
confidence: 70%
“…Some studies have shown a positive relationship between age and resilience (Bolognini et al, 1996;St. Jean et al, 2001;Frost and McKelvie, 2004;Sun and Stewart, 2007;Salazar-Pousada et al, 2010;Torma, 2010;Wagnild, 2011;Gooding et al, 2011) while others reported that resilience decreases with age (Condly, 2006;Schoon, 2006;Riches et al, 2009). Evidently, most of the existing studies have investigated age effects on resilience within the same cohort of adolescents or between children and adolescents while others were among young adults and older adults.…”
Section: Age and Resiliencementioning
confidence: 99%
“…In relation to the trait conceptualization, these characteristics or individual 1 differences, which are more commonly referred to as protective factors in the resilience 2 literature, have been examined extensively by scholars seeking to identify the qualities of 3 resilient individuals (see, for a review, Luthar, 2006;Masten & Reed, 2002;Rutter, 2000). In 4 terms of the extant research in this area, studies have been conducted with high-risk children 5 (see, for a review, Condly, 2006) and, more recently, with adults, families and communities 6 that have been exposed to potentially stressful circumstances, such as the death of a close However, due to the contextual specificity of resilience (Luthar et al, 2000), the findings of 14 this work are not easily applicable to high achievers who actively seek to engage with 15 challenging situations that present opportunities for them to raise their performance level, as 16 opposed to clinical populations who have essentially been "forced" to exhibit resilience 17 qualities in order to maintain functioning. 18 A burgeoning body of evidence points to the importance of managing stress in attaining 19 the highest levels of sport performance (Gould & Maynard, 2009 22 two overall categories linked to resilience: the overall handling of pressure and adversity (i.e., 23 the capacity to deal with routine stressors of training and competition), and the psychological 24 characteristics to overcome (i.e., the capacity to deal with potentially more extreme stressors, 25 such as long-term illness).…”
Section: Psychological Resilience In Olympic Championsmentioning
confidence: 99%
“…Akademik başarı gösteren dirençli öğrencilere yönelik yapılan çalışmalar, bazı öğrenciler başarılı olurken benzer geçmişe ve hayat tecrübesine sahip akranlarının neden başarılı olamadığını anlamamıza yardımcı olmaktadır (Grassi, 2014;Padron, Waxman ve Lee, 2012). Zorlu koşulların üstesinden gelerek başarıyı yakalayan dirençli öğrencilerin başarılarını yordayan değişkenlerin belirlenmesi alan yazınında daha da önem kazanmaya başlamıştır (Condly, 2006;Grassi, 2014). Dirençli öğrencilerin eğitim yaşantılarında nasıl başarılı kalabildiklerini ve başarısızlıkların nedenlerini irdelemek daha çok akademik başarıyı yordayan değişkenlere odaklanmamızı sağlayacaktır (Grassi, 2014;Waxman ve Huang, 1996).…”
Section: Introductionunclassified